Discourse on Regulation and Implementation of Labor Supervision in Indonesia - Weny A DUNGGA; Sudarsono SUDARSONO; Abd.Rachmad BUDIONO; Rachmat SAFAAT (Indonesia Strategic Sustainability, 2023)
Labor supervision affects employment conditions in a country. The study was conducted on the regulation of Labor supervision in Indonesia and the form of follow-up of Labor supervision in labor regulation in Indonesia. The statute, case, and conceptual approaches normatively support problem analysis. The study showed that in realizing the protection of workers, presenting a harmonious employment relationship did not materialize due to disparities until the transition of the Labor Supervision Authority between local government units and the central government, which became the discourse of labor so that the purpose of Labor supervision is not fully realized. The problem is increasingly complex with the birth of a substantively problematic job creation Perppu, the lack of labor inspectors with a wide area of work and workload technically tiered, labor conditions in emergencies, as well as the massive flow of foreign workers to Indonesia can be solved with the renewal of labor which includes fundamental changes certainly made to the substance of, changes in labor supervision mechanisms that emphasize more on factual supervision by going directly to places or areas that have labor problems, regulation of the form of Labor supervision in the work area and workload and certain emergency conditions, as well as the active involvement of unions in the labor supervision process.